STRATEGI PEMASARAN PASAR SENI GUWANG SUKAWATI SEBAGAI DAYA TARIK WISATA BELANJA - Dewi, Luh Kartika Sutra; Mahadewi, NPE.; Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 1 (2020): Jurnal IPTA (July 2020), 2020)
Guwang Art Market is one of traditional art market in Sukawati sub-district, Gianyar Regency. Along with technological advances and the rise of the modern art market, the traditional art market has begun to be abandoned. This study was conducted to determine the right marketing strategy to maintain the existence of the Guwang Art Market as a shopping tourist attraction. The data analysis technique used are internal external/IFAS EFAS factors with used the Marketing Mix 7Ps as an internal factor and the external factors analysis used are markets, competitors, government, technology, economics, social and culture. The type of data used a quantitative and qualitative data, primary and secondary data. Data collection techniques by observation, interviews, internal questionnaires were distributed to 175 tourists who visited at Guwang Art Market, then external questionnaires for the Management, Tourism Academics and Freelance Guide. Data analysis technique used a mix methods. The results of this study from 22 indicators of the internal environment and the external environment from 13 indicators, then obtained as 13 strength factors, 9 weakness factors, 8 opportunity factors and 5 threat factors. Based on the results of used internal external/IFAS EFAS factors it is known that the total value of IFAS is 2,53 and the total value of EFAS is 2,70 so that it shows the position of the Guwang Art Market is in cell V, namely the Growth Stability Strategy or the Guwang Art Market wants growth or improvement their business going to forward and overcoming the current of income slump.